2017
DOI: 10.1302/2046-3758.63.bjr-2016-0237.r1
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin E3 ligase Itch negatively regulates osteoblast function by promoting proteasome degradation of osteogenic proteins

Abstract: ObjectivesUbiquitin E3 ligase-mediated protein degradation regulates osteoblast function. Itch, an E3 ligase, affects numerous cell functions by regulating ubiquitination and proteasomal degradation of related proteins. However, the Itch-related cellular and molecular mechanisms by which osteoblast differentiation and function are elevated during bone fracture repair are as yet unknown.MethodsWe examined the expression levels of E3 ligases and NF-κB members in callus samples during bone fracture repair by quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 30 publications
(43 reference statements)
2
27
0
Order By: Relevance
“…HERC4 belongs to the HERC family of ubiquitin ligases and encodes HECT and RLD domain containing E3 ubiquitin protein ligase 4 . A recent mouse study demonstrated that ubiquitin E3 ligases, involved in protein degradation, regulate osteoblast function . Therefore, it is plausible that HERC4 might be also important in the pathophysiology of ONJ.…”
Section: Discussionsupporting
confidence: 78%
“…HERC4 belongs to the HERC family of ubiquitin ligases and encodes HECT and RLD domain containing E3 ubiquitin protein ligase 4 . A recent mouse study demonstrated that ubiquitin E3 ligases, involved in protein degradation, regulate osteoblast function . Therefore, it is plausible that HERC4 might be also important in the pathophysiology of ONJ.…”
Section: Discussionsupporting
confidence: 78%
“…Proteins common to bone and other biomineralization systems found in the inner ear of adult black bream ( Acanthopagrus butcheri , n = 3) . In addition to structural collagens and proteoglycans, we also found proteins that are associated with osteoblast function or otherwise act as substrates for extracellular matrix formation .…”
Section: Discussionmentioning
confidence: 80%
“…In addition to the 'usual' otolith proteins, we found high abundances of bone and cartilage type proteoglycans (Mimecan (Osteoglycin), Epiphycan, Biglycan, Decorin, Aggrecan), Collagen types I and II, and osteoblast regulating proteins (e.g. E3 ligase itchy-like) [11, [49][50][51][52]. Importantly, we found no evidence of protein markers for osteoclastic function.…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations